2007
DOI: 10.1086/517956
|View full text |Cite
|
Sign up to set email alerts
|

Importation ofAcinetobacter baumanniiInto a Burn Unit: A Recurrent Outbreak of Infection Associated With Widespread Environmental Contamination

Abstract: A burn patient was infected withAcinetobacter baumanniion transfer to the hospital after a terrorist attack. Two patients experienced cross-infection. Environmental swab samples were negative forA. baumannii. Six months later, the bacteria reemerged in 6 Patients. Environmental swab samples obtained at this time were inoculated into a minimal mineral broth, and culture results showed widespread contamination. No case of infection occurred after closure of the unit for disinfection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(37 citation statements)
references
References 13 publications
(10 reference statements)
1
31
1
1
Order By: Relevance
“…Several Acinetobacter outbreaks in burn units were described previously and were partially associated with extensive environmental contamination (42)(43)(44)(45). A. baumannii survives in the hospital environment for a prolonged period, even on dry surfaces and the hands of health care personnel, and the carriage of MDRAB in human hosts may also be prolonged (10,46,47), which can facilitate transmission and outbreaks of A. baumannii.…”
Section: Discussionmentioning
confidence: 96%
“…Several Acinetobacter outbreaks in burn units were described previously and were partially associated with extensive environmental contamination (42)(43)(44)(45). A. baumannii survives in the hospital environment for a prolonged period, even on dry surfaces and the hands of health care personnel, and the carriage of MDRAB in human hosts may also be prolonged (10,46,47), which can facilitate transmission and outbreaks of A. baumannii.…”
Section: Discussionmentioning
confidence: 96%
“…Carbapenems are considered the first-line drugs for treatment of A. baumannii infections in Iran; however, resistance to these drugs is increasing owing to the overexpression of efflux pumps and to the ability of the bacterium to produce different carbapenemases, in particular class D carbapenemases [1,2,5,6]. A. baumannii is increasingly causing infections in burn units worldwide including Iran [7][8][9]. In addition, A. baumannii strains resistant to different classes of antibiotics including carbapenems have reportedly been isolated from burn patients in Iran [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Closed-suctioning system minimizes environmental contamination and was thus preferred as suggested previously [16]. Some studies have reported complete sealing of units for control the outbreaks [15,16].…”
Section: Discussionmentioning
confidence: 99%